IMPLEMENTASI MUHASABAH DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA DI PONDOK PESANTREN - Irna Puspita; Mita Febriyanti; Septika Amanda; Agus Sukirno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic boarding schools (pesantren) as Islamic educational institutions have unique ways of developing personality, including through self-reflection or muhasabah. However, research specifically integrating muhasabah into guidance and counseling services to shape the disciplined character of students is still very limited. This study aims to analyze the concept, its implementation, and the role of muhasabah in guidance and counseling services at Islamic boarding schools, as a way to shape disciplined attitudes in Islamic boarding schools. This study used a systematic literature review (SLR) method by examining various scientific sources published in the last ten years. The results show that muhasabah functions as an effective internal method to increase self-awareness, emotional control, and self-regulation in students. Its implementation in Islamic boarding schools is carried out through several organized activities, such as daily muhasabah, evening muhasabah, halaqah (religious discussion), and reflective journals. These four activities can be integrated neatly and systematically into counseling services, both for individuals and groups. The synergy between self-reflection, an internal factor, and the Islamic boarding school education system, an external factor, has been proven to foster a sense of discipline that grows from within and persists, not simply due to fear of external scrutiny. However, its effectiveness depends on the individual's level of awareness and preparation and still faces limitations in empirical measurement. Innovation is needed in implementing self-reflection to remain relevant to today's digital age, including using technology-based counseling approaches while still adhering to Islamic values.